2017
DOI: 10.1016/j.earlhumdev.2017.09.013
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prenatal substance use and maternal contingent responsiveness on infant affect

Abstract: Background The effects of prenatal substance exposure on neurobehavioral outcomes are inherently confounded by the effects of the postnatal environment, making it difficult to disentangle their influence. The goal of this study was to examine the contributing effects of prenatal substance use and parenting style (operationalized as contingent responding during the play episodes of the Still-face paradigm [SFP]) on infant affect. Methods A prospective cohort design was utilized with repeated assessment of sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 69 publications
0
26
0
Order By: Relevance
“…The ENRICH study methodology has been described elsewhere [4, 17, 18]. Briefly, patients receiving prenatal care at UNM-affiliated clinics in the Albuquerque, NM metropolitan area are invited to participate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ENRICH study methodology has been described elsewhere [4, 17, 18]. Briefly, patients receiving prenatal care at UNM-affiliated clinics in the Albuquerque, NM metropolitan area are invited to participate.…”
Section: Methodsmentioning
confidence: 99%
“…Recent estimates show that nearly one-fourth of pregnant women in the U.S. fill a prescription for opioids [1], while gestational opioid use has increased five-fold from 1999 to 2013 [2]. For pregnant women with opioid use disorder (OUD), medication assisted therapy (MAT) is associated with improved perinatal outcomes, decreased risk of relapse, and lower rates of maternal criminal involvement [3, 4]. While adverse outcomes are lower among women on MAT, many infants with prenatal opioid exposure (POE) − whether illicit, prescription, or MAT – have neonatal opioid withdrawal syndrome (NOWS), which is now estimated to affect as many as 2% of all births [5].…”
Section: Introductionmentioning
confidence: 99%
“…The third of these, from our own cohort, utilized the still‐face paradigm (SFP) in 6‐month‐old infants. We found significantly lower positive infant affect across repeated measures in the univariate analyses, but these differences did not reach significance after adjusting for covariates (Lowe et al., ).…”
Section: Resultsmentioning
confidence: 76%
“…Early‐life experiences have been shown to affect brain development dramatically and produce measurable, long‐lasting alterations in specific regions of the brain that are associated with behavioral and cognitive functioning (Graham et al., ; Smith et al., ). Our own research has suggested that supportive parenting interaction style, which is modifiable through teaching and specialized support, might be a key early intervention area that could benefit NDB outcomes in alcohol‐ and drug‐exposed infants during the first year of life (Lowe et al., ). Future studies can use the information in this report to more closely investigate and identify which assessments or assessment domains should become the focus of research and, ultimately, shape clinical guidelines for infant evaluations and the development of early interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we were not able to include measures of socioeconomic status in this report, as this variable was only collected from participants after enrollment in the ENRICH cohort. A prior report of ENRICH cohort participants indicate that annual household income <$20,000 is more than twice as prevalent among OUD/MAT participants compared to those without OUD/MAT (Lowe et al, 2017). Thus, in addition to the increased risks associated with polysubstance use among MAT patients, poverty represents an important consideration when planning early interventions.…”
Section: Discussionmentioning
confidence: 99%